Assortative Mating and Couple Taxation: A Note - Giacomo Corneo (CESifo GmbH, 2025)
An often neglected implication of couple taxation is its impact on marital sorting. A tractable model of such an impact is offered in this paper. It reveals that, as compared to joint taxation with income splitting, individual taxation makes higher-ability individuals more picky in the marriage market, which translates into a higher degree of economic homogamy in society. Furthermore, a shift from joint to individual taxation is predicted to reduce the average quality of marriages in the population.
Keywords: H21; H24; 330; economic homogamy; assortative mating; couple taxation; tax unit; progressive income tax